Identification of a Novel Membrane-Associated Gene Product That Suppresses Toxicity of a TrfA Peptide from Plasmid RK2 and Its Relationship to the DnaA Host Initiation Protein - Kim, Peter D. (American Society for Microbiology, 2003)
The toxicity of a peptide derived from the amino-terminal portion of 33-kDa TrfA, one of the initiation proteins encoded by the broad-host-range plasmid RK2, was suppressed by a host protein related to DnaA, the initiation protein of Escherichia coli. The newly identified 28.4-kDa protein, termed a DnaA paralog (Dp) because it is similar to a region of DnaA but likely has a different function in initiation of plasmid RK2 replication, interacts physically with the 33-kDa TrfA initiation protein, including the initiation-active monomeric form. The Dp has a cellular distribution similar to that of the 33-kDa TrfA initiation protein, being found primarily in the inner membrane fraction, with lesser amounts detected in the outer membrane fraction and almost none in the soluble fraction of E. coli. Maintenance and inner membrane-associated replication of plasmid RK2 were enhanced in a Dp knockout strain and inhibited in strains containing extra copies of the Dp gene or in membrane extracts to which a tagged form of Dp was added. Recently, the Dp was independently shown to help prevent overinitiation in E. coli and was termed Hda (S. Kato and T. Katayama, EMBO J. 20:4253-4262, 2001).